Swatting flies: modelling wound healing and inflammation in Drosophila. - Razzell, W.; Wood, W.; Martin, P. (Disease models & mechanisms, 2011)
Aberrant wound healing can lead to a variety of human pathologies, from non-healing chronic wounds that can become dangerously infected, to exuberant fibrotic healing in which repair is accompanied by excessive inflammation. To guide therapeutic intervention, we need a better understanding of the fundamental mechanisms driving tissue repair; this will require complementary wound-healing studies in several model organisms. Drosophila has been used to model genetic aspects of numerous human pathologies, and is being used increasingly to gain insight into the molecular and genetic aspects of tissue repair and inflammation, which have classically been modelled in mice or cultured cells. This review discusses the advantages and disadvantages of Drosophila as a wound-healing model, as well as some exciting new research opportunities that will be enabled by its use.